Risk factor assessment on rare mammal species (saiga) during road construction in Central Kazakhstan - Nargiza Askarova (Research Retrieval and Academic Letters, 2024)
The study addresses the importance of investigating risk factors for the mammal species, namely for saiga during road construction in Central Kazakhstan. The research provides information about saiga populations and their special characteristics as a feature to identify risks on them. It further evaluates the risk factors on saiga population and migration during constructing A17 motorway in the Central Kazakhstan region. Moreover, the study proposes recommendations at enhancing the effectiveness of procedures and measures aiming to tackle high impacts on rare saiga species.